La desintegración familiar y su incidencia en el desarrollo del lenguaje de los niños y niñas de 4 y 5 años con síndrome de down que asisten a la fundación “Amigos del arca Ecuador”, del cantón Puerto Quito, provincia de Pichincha. Período 2014-2015”. Lineamientos propositivos - Moreira Loo, Diana Mercy r (2015)
This thesis refers to "family disintegration and ITS IMPACT ON THE DEVELOPMENT OF THE LANGUAGE OF CHILDREN OF 4 AND 5 YEARS WITH DOWN SYNDROME FOUNDATION ATTENDING THE" FRIENDS OF ARCA ECUADOR "Puerto Quito Canton OF PROVINCE PICHINCHA. PERIOD 2014-2015 ". GUIDELINES proactive "and aims to study one of the problems more incidents in our country as it is family disintegration and the relationship with the language of children with Down syndrome because this is affected in the developed; it was realized to meet a requirement prior to choose a degree in career Psicorrehabilitación and Special Education, meeting the established standards for graduation at the National University of Loja. In this research the overall objective raised was: To determine the incidence of family breakdown in language development of children aged 4 and 5 years old with Down syndrome attending the foundation "Friends of Arca Ecuador" Canton Puerto Quito, Pichincha Province. The methods used for the preparation of this research work were: Scientist, Analytical Synthetic, inductive, deductive, Descriptive and Statistical Model; the techniques used were: a survey of Parents of children aged 4 and 5 years old with Down syndrome attending the foundation "Friends of Arca Ecuador", the canton Puerto Quito, Pichincha Province. Period 2014-2015, to establish family disintegration of their homes; Zimmerman and test applied to children aged 4 and 5 years with Down syndrome attending the foundation "Friends of Arca Ecuador", the canton Puerto Quito, Pichincha Province. Period 2014-2015, to evaluate the development of language. It analyzed the results of the survey of parents, came to the following conclusion. 80% of respondents Parents report that the child's family consists of father, mother and children; 12% for mother and child; 4% for parents and children; and 4% for grandparents and grandchildren. According to the test results of Test Zimmerman concludes that: 48% of children surveyed girls are in the range of 30-40 which corresponds to a development of Language Oral Normal, 28% is located in the range 50 to 80 equivalent to 24% and excellent in the range of 10 to 20 corresponding to Low.